Sarcoglottis wernerherzogii (Spiranthinae) : a new species from Cusco, Peru - Collantes Meza, Benjamín; Edquen Oblitas, José Dilmer; Incahuamán, Feliciano; Salazar Chávez, Gerardo Adolfo 1961- (2023)
A new species of Sarcoglottis from the department of Cusco, Peru is described and illustrated as S. wernerherzogii. It is similar to eastern South American S. fasciculata but distinguished by its contrasting habitat (high-Andean montane cloud forest as 2050−2500 m a.s.l. vs. Atlantic rain forest near sea level), flowering after the shed-ding of the leaves (vs. flowering with leaves present); homogeneous green or yellow flowers (vs. whitish or pale green with contrasting reddish veins); rigidly conduplicate-concave lateral sepals that, when spread out are strongly falcate (vs. slightly concave, not rigid, obliquely lanceolate lateral sepals); strongly cymbiform, obovate hypochile as wide as long when spread out (vs. broadly channeled, oblanceolate hypochile about twice longer than wide or longer when spread out); ovate, strongly deflexed epichile provided with a central longitudinal thickening throughout its length (vs.erect or gently arcuate epichile with a thickening only at the apex); and apical anther beak truncate (vs. apical anther beak rounded). The strongly cymbiform hypochile that, when spread out is as wide as long, is unique in the genus. The differences between S. fasciculata, the new species, and other Peruvian species of Sarcoglottis are contrasted in a table. Sarcoglottis wernerherzogii is known from less than a dozen plants in two populations, both under nominal protection in the Machupicchu Historical Sanctuary and the Area of Conservación Regional Choquequirao, respectively. The status "DD" (data deficient) is suggested until an objective assessment of its risk status can be carried out.
Se describe e ilustra una nueva especie de Sarcoglottis del departamento de Cusco, Perú como S. wernerherzogii. Es similar a S. fasciculata del este de Sudamérica, pero se distingue en sus hábitat contrastante (bosque montano nublado andino a 2050−2500 m s.n.m. vs. bosque lluvioso atlántico cerca del nivel del mar); floración tras la caída de las hojas (vs. floración con las hojas presentes); flores homogéneamente verdes o amarillas (vs. flores blanquecinas o verde pálido con venas rojizas contrastantes); sépalos laterales rígidamente conduplicado-cóncavos, al extender fuertemente falcados (vs. sépalos laterales ligeramente cóncavos, no rígidos, al extender oblicuamente lanceolados); hipoquilo fuertemente cymbiforme, al extenderlo obovado, casi tan ancho como largo (vs. hipoquilo acanalado, al extenderlo oblanceolado, ca. dos veces más largo que ancho o más largo); epiquilo ovado, fuertemente deflexo, provisto de un engrosamiento central longitudinal en toda su longitud (vs. epiquilo triangular, erecto o ligeramente arqueado, engrosado solo en el ápice); y pico de la antera truncado (vs. redondeado). El hipoquilo fuertemente cymbiforme que al ser extendido es tan ancho como largo es único en el género. Las características que distinguen a S. fasciculata, la nueva especie y otros Sarcoglottis peruanos son contrastados en forma tabular. Sarcoglottis wernerherzogii es conocida de menos de una docena de plantas y dos poblaciones, ambas bajo protección nominal en el Santuario Histórico de Machupicchu y el Área de Conservación Regional Choquequirao, respectivamente. Se sugiere el estatus "DD" (datos deficientes) hasta que sea posible llevar a cabo una evaluación objetiva de su estatus de riesgo.
Keywords: ORQUÍDEAS -- IDENTIFICACIÓN -- CUSCO (PERÚ); ORQUÍDEAS -- VARIEDADES -- PERÚ; ORQUÍDEAS -- CONSERVACIÓN -- PERÚ